MicroRNA-mediated gene silencing modulates the UV-induced DNA-damage response - Pothof, Joris (Nature Publishing Group, 2009)
DNA damage provokes DNA repair, cell-cycle regulation and apoptosis. This DNA-damage response encompasses gene-expression regulation at the transcriptional and post-translational levels. We show that cellular responses to UV-induced DNA damage are also regulated at the post-transcriptional level by microRNAs. Survival and checkpoint response after UV damage was severely reduced on microRNA-mediated gene-silencing inhibition by knocking down essential components of the microRNA-processing pathway (Dicer and Ago2). UV damage triggered a cell-cycle-dependent relocalization of Ago2 into stress granules and various microRNA-expression changes. Ago2 relocalization required CDK activity, but was independent of ATM/ATR checkpoint signalling, whereas UV-responsive microRNA expression was only partially ATM/ATR independent. Both microRNA-expression changes and stress-granule formation were most pronounced within the first hours after genotoxic stress, suggesting that microRNA-mediated gene regulation operates earlier than most transcriptional responses. The functionality of the microRNA response is illustrated by the UV-inducible miR-16 that downregulates checkpoint-gene CDC25a and regulates cell proliferation. We conclude that microRNA-mediated gene regulation adds a new dimension to the DNA-damage response.